EVALUATION OF MAMMARY GLAND PROSTHESIS ROTATION PROPHILAXIS EFFICIENCY IN A THREE YEARS POSTOPERATIVE PERIOD - Zakhartseva , O.I.; Mishalov , V.G.; Khrapach , V.V.; Markulan , L.Yu. (The Ukrainian Scientific Medical Youth Journal, 2018)
Mammary gland prosthesis rotation (MGPR) after augmentation mammoplasty –poorly studied complication of plastic surgery. The frequency of MGPR is not well known. There are indications that MGPR of 900, which is considered clinically significant, ranges from 0.9% to 14%. Preventing methods of MGPR are not developed enough.Goals: Determination of the effectiveness of the upper pole reinforcement of «neo pocket» with prolen thread for the prevention of MGPR after primary augmentative mammoplasty in a three years of postoperative period.Materials and methods: The invectigation is performed on the basis of the Surgery Department No. 4 of Bogomolets NMU in the period from 2013 to 2018 A prospective, independent comparison of the primary augmentative mammaplasty results between three independent groups of patients was performed: two groups of comparison and one main groups. The first group of comparison (Group P1) included 94 patients who evaluated the results of augmentative mammaplasty one year after the operation, the second comparison group (Group P3) – 63 patients three years after this operation. The main group (group O) included 76 patients who had a prospective study after one (group O1) and then three years later (group O3) – 62 patients. In the comparison groups, the standard PAMP was performed, in the main group – according to the developed method. The patients were not diferenciated statistically by age, body mass index (BMI), weight of prostheses, percentage of pregnant women and patients with lactation period. In all cases, textured prostheses with high and medium profile were implanted. The majority of patients were operated with prostheses from 325-335 ml and 375 ml. The MGPR evaluation was carried out in accordance with the developed method using the ultrasound of the ESAOTE firmware model Technos Partner with a linear sensor with a frequency of 12.5 MHz. Data analysis was performed using the IBM SPSS Statistics 22 statistical analysis packets.Results: one year after the operation in the P1 group, a slightly lower, but not reliable percentage of prosthesis rotation – 143 (76.1%) against 103 (81.7%) in the group P3, p = 0.231, was diagnosed. At  the  same time, in the P1 group only 4 (4.3%) women did not have the rotation of the prosthetics of both MG and in the P3 group 2 women (3.2%), p = 0.001. Significant difference of the frequency of patients with clinically significant MGPR: 11 (11.7%) patients in the P1 group versus 12 (19.0%) in the P3 group (p = 0.202) and 13 (6.9%) in the P1 group against 13 (10.3%) of the prostheses in the group P3 (p = 0.284). In patients in the main group, a small (30.9%) frequency of clinically insignificant MGPR was noticed after PAMP and it did not increase after the three years period (32.1%). In the P1 group, 143 (76.1%) prostheses were diagnosed with rotation, in the group O1 – 46 (30.3%), p = 0.001. At the same time, in the P1 group, only 4 (1.6%) women didn‘t have the rotation of the of both MG prostheses and in the group 39 (51.3%), p = 0.001, which indicates the effectiveness of the developed methodology. A similar trend was observed in the case of comparison of the three years results between the group P3 and the group O3. The absence of rotation of prostheses was diagnosed in 83 (66.9%) O3 groups and 26 (20.6%) in the P group, and there was no clinically significant rotation of O3 patients versus group P where these patients were observed: 12 (19.0% ), p = 0.001.Conclusion: A method of fixation of the submuscular «neo pocket» upper pole with prolen thread, provides stable protective effect of MGPR and gives a possibility to avoid a clinically significant rotation(more than 900) throughout a three years after augmentative mammoplasty comparing with a traditional method-11,7 %, patients in a year-19%, in a three years after PAMP, р<0,01.